Kandungan Antioksidan pada Suplemen Daun Kelor terhadap Kadar Acyl Ghrelin pada Subjek Obesitas - Mahabatillah, Desty; Afifah, Diana Nur; Pramono, Adriyan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the effect of antioxidant content on acyl ghrelin levels in obese subjects. This research method is a systematic literature review approach by searching for journal articles in the PubMed database. Inclusion criteria were articles published in the last 10 years using RCT methods on experimental animals and humans with obese nutritional status and providing Moringa leaf intervention. The research results showed that of 69 articles identified, only 7 articles met the inclusion criteria. The findings obtained indicate that the high antioxidant content of Moringa leaves has great potential as a functional food source and is beneficial for body health. The conclusion of the research is that the antioxidant content in Moringa leaves has an effect on obesity and still needs to be studied for its effect on acyl ghrelin. Keywords: Acyl ghrelin, Moringa Leaf Supplements, Antioxidants, Obesity